PSYCHO-PHYSICAL STATE AS THE BASIS FOR THE MANIFESTATION OF SPECIAL PHYSICAL FITNESS OF YOUNG SKI RACERS - Kostareva, S.V.; Popova, A.I.; Gorbunov, S.S.; Ibragimov, R.R. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to substantiate the concept of "psychophysical state" and to reveal its connection with the special physical fitness of young ski racers. Methods and structure of the study. The conducted scientific work is based on the method of theoretical analysis and generalization of scientific and methodological literature. Results and conclusions. In the course of theoretical analysis, the concepts of "psychophysical qualities" and "psychophysical state" are revealed. The significance of the physical and mental readiness of ski racers during the transition from the stage of initial training to the stage of sports specialization has been revealed. The requirements for the special physical fitness of young athletes at the stage of initial specialization are determined. The main features of this stage include the emergence of control measures, including standards for special physical training in the form of ski racing in classic and free style, as well as an increase in the number of control and main starts. At the same time, high demands are made on the technique of skiing.